(untitled) (Pedagogical Horizons, 2021)
The article examines models of religious pluralism in children’s books about ‘world religions’. It asks how successful these books are in fostering sensibility towards religious difference and in promoting a competence to deal with religious pluralism. The sample consists of approximately twenty children’s books of this recent genre – published in German from 1998 to 2018. As a result, it will be argued that a religious-phenomenological and anthropological universalist account dominate implicit and explicit models of pluralism. Despite severe criticism from the side of a postcolonial and cultural study of religion, the category of world religions is prominent in the sample. Reasons for its persistence can be seen in Christian cultural dominance and protestant conceptual influence on the reification of ‘religion’ in the respective area as well as the successful semantic simplification of the category.